Ketahanan Organisasi Kantor Imigrasi Kelas I Khusus Non TPI Jakarta Selatan dalam Menghadapi Penyalahgunaan Izin Tinggal Penanam Modal Asing - Rivando, Boy; Samputra, Palupi Lindiasari (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
The entry of foreigners into Indonesia can improve the economy and increase the country's foreign exchange through tourism and investment. However, if the residence permit given to foreign citizens is misused, it could pose various threats to Indonesia's security. Moreover, currently a circular has been issued regarding administrative convenience for foreign investors. For this reason, strong organizational resilience is needed from immigration agencies, especially the South Jakarta Immigration Office so that they can continue to carry out their immigration functions in the face of incoming threats. The aim of this research is to analyze the organizational resilience of the South Jakarta Immigration Office in dealing with misuse of foreign investors' residence permits. The research method used is a qualitative approach. Data collection techniques can take the form of in-depth interviews. The approach used in this research is the organizational resilience approach. The results of this research show that the organizational resilience of the Immigration Office South Jakarta is able to withstand changes in the flow of procedures for foreign investors which creates opportunities for abuse of residence permits. The South Jakarta Immigration Office has tried to fulfill existing demands. However, there are still several shortcomings and limitations in implementing these resilience efforts